The frequency of high PD-L1 expression is low in lung adenocarcinoma patients from Northeast Brazil - Antonio V. Alves da Silva; Francisco Martins Neto; Ana Claudia da Silva M. de Oliveira; Benedito A. Carneiro; Marclesson Alves; Cleto Dantas Nogueira; Fabio Tavora (BMC, 2019)
Abstract Background As Immune checkpoint inhibitors (ICPIs) are changing the standard-care in lung cancer with good clinical activities and durable responses, its indication must be based on the appropriate patient selection once only a fraction of patients has a response to these costly drugs. In larger cohorts the expression of programmed cell death-ligand 1 (PD-L1) has been associated with good clinical response of ICPIs in lung adenocarcinoma where the rate of high PD-L1 expression (defined as PD-L1tumor proportion score ≥ 50%) is ~ 30%, but once rare studies are available addressing the frequency of PD-L1 in populations outside those cohorts, we aimed to report the prevalence of PD-L1 and the frequency of patients with high PD-L1 expression utilizing data from a major pathology laboratory in Northeastern Brazil. Methods We retrospectively evaluated the PD-L1 expression in 158 surgically resected primary lung adenocarcinoma including 158 with anaplastic lymphoma kinase (ALK) expression. PD-L1 and ALK expression were evaluated by immunohistochemical analysis with the SP263 and D5F3 assays, respectively. Results Of the 158 samples analyzed, 94 (59.5%) had a PD-L1 tumor proportion score (TPS) < 1%, 38 (24.0%) had a PD-L1 TPS of 1-49% and 26 (16.5%) had a PD-L1 TPS of ≥50%. ALK expression was detected in 21 (13.3%) of the 158 tumor samples and 5 (3.2%) of them had a PD-L1 TPS of ≥50%. Conclusion The frequency of strong PD-L1 expression was lower than that previously reported in the trials where PD-L1 expression was used as a biomarker for patient selection. Also, considering that a subset of patients with ALK positivity had a strong PD-L1 expression, further studies will be required to examine the efficacy of PD-1/PD-L1 inhibitors in such patients.